Evaluate the integral:


Evaluate the integral:

$\int \frac{x}{x^{2}+3 x+2} d x$


$I=\int \frac{x}{x^{2}+3 x+2} d x$

As we can see that there is a term of $x$ in numerator and derivative of $x^{2}$ is also $2 x$. So there is a chance that we can make substitution for $x^{2}+3 x+2$ and I can be reduced to a fundamental integration.

As, $\frac{\mathrm{d}}{\mathrm{dx}}\left(\mathrm{x}^{2}+3 \mathrm{x}+2\right)=2 \mathrm{x}+3$

$\therefore$ Let, $x=A(2 x+3)+B$

$\Rightarrow x=2 A x+3 A+B$

On comparing both sides -

We have,

$2 A=1 \Rightarrow A=1 / 2$

$3 A+B=0 \Rightarrow B=-3 A=-3 / 2$


$I=\int \frac{\frac{1}{2}(2 x+3)-\frac{3}{2}}{x^{2}+3 x+2} d x$

$\therefore I=\frac{1}{2} \int \frac{2 x+3}{x^{2}+3 x+2} d x-\frac{3}{2} \int \frac{1}{x^{2}+3 x+2} d x$

Let, $I_{1}=\frac{1}{2} \int \frac{2 x+3}{x^{2}+3 x+2} d x$ and $I_{2}=\frac{3}{2} \int \frac{1}{x^{2}+3 x+2} d x$

Now, $I=I_{1}-I_{2} \ldots .$ eqn $I$

We will solve $I_{1}$ and $I_{2}$ individually.

As, $I_{1}=\frac{1}{2} \int \frac{2 x+3}{x^{2}+3 x+2} d x$

Let $u=x^{2}+3 x+2 \Rightarrow d u=(2 x+3) d x$

$\therefore$ I $_{1}$ reduces to $\frac{1}{2} \int \frac{\mathrm{du}}{\mathrm{u}}$


$\mathrm{I}_{1}=\frac{1}{2} \int \frac{\mathrm{du}}{\mathrm{u}}=\frac{1}{2} \log |\mathrm{u}|+\mathrm{C}\left\{\because \int \frac{\mathrm{dx}}{\mathrm{x}}=\log |\mathrm{x}|+\mathrm{C}\right\}$

On substituting value of $u$, we have:

$I_{1}=\frac{1}{2} \log \left|x^{2}+3 x+2\right|+C \ldots .$ eqn 2

As, $I_{2}=\frac{3}{2} \int \frac{1}{x^{2}+3 x+2} d x$ and we don't have any derivative of function present in denominator. $\therefore$ we will use some special integrals to solve the problem.

As denominator doesn't have any square root term. So one of the following two integrals will solve the problem.

i) $\int \frac{1}{x^{2}-a^{2}} d x=\frac{1}{2 a} \log \left|\frac{x-a}{x+a}\right|+C$ ii) $\int \frac{1}{x^{2}+a^{2}} d x=\frac{1}{a} \tan ^{-1}\left(\frac{x}{a}\right)+C$

Now we have to reduce $I_{2}$ such that it matches with any of above two forms.

We will make to create a complete square so that no individual term of $x$ is seen in denominator.

$\therefore I_{2}=\frac{3}{2} \int \frac{1}{x^{2}+3 x+2} d x$

$\Rightarrow I_{2}=\frac{3}{2} \int \frac{1}{\left\{x^{2}+2\left(\frac{3}{2}\right) x+\left(\frac{2}{2}\right)^{2}\right\}+2-\left(\frac{2}{2}\right)^{2}} d x$

Using: $a^{2}+2 a b+b^{2}=(a+b)^{2}$

We have:

$I_{2}=\frac{3}{2} \int \frac{1}{\left(x+\frac{2}{2}\right)^{2}-\left(\frac{1}{2}\right)^{2}} d x$

$\mathrm{I}_{2}$ matches with $\int \frac{1}{\mathrm{x}^{2}-\mathrm{a}^{2}} \mathrm{dx}=\frac{1}{2 \mathrm{a}} \log \left|\frac{\mathrm{x}-\mathrm{a}}{\mathrm{x}+\mathrm{a}}\right|+\mathrm{C}$

$\therefore I_{2}=\frac{3}{2}\left\{\frac{1}{2\left(\frac{1}{2}\right)} \log \left|\frac{\left(x+\frac{3}{2}\right)-\frac{1}{2}}{\left(x+\frac{3}{2}\right)+\frac{1}{2}}\right|+C\right\}$

$\Rightarrow I_{2}=\frac{3}{2} \log \left|\frac{2 x+3-1}{2 x+3+1}\right|+C$

$\Rightarrow I_{2}=\frac{3}{2} \log \left|\frac{2 x+2}{2 x+4}\right|+C=\frac{3}{2} \log \left|\frac{x+1}{x+2}\right|+C \ldots$ eqn 3

From eqn 1:


Using eqn 2 and eqn 3:

$I=\frac{1}{2} \log \left|x^{2}+3 x+2\right|+\frac{3}{2} \log \left|\frac{x+1}{x+2}\right|+C$

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now